EFEKTIFITAS KOMUNIKASI KESEHATAN DOKTER DALAM MENDIAGNOSIS PENYAKIT PASIEN ANGGOTA KPPS PEMILU 2019 DI KOTA PEKANBARU - Suci Shinta Lestari; Muhammad David Hendra (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
Communication between doctor and patient is the most important component in providing health care. A doctor's professional attitude is shown when dealing with his duties, which means being able to complete his duties according to his role and function; able to manage themselves such as punctuality, division of professional duties with other personal tasks and able to deal with various types of patients and able to cooperate with other health professions. The professional attitude of a doctor will be seen from the patient handling process which will be a measure of success and professionalism. In this study, researchers looked at the effectiveness of medical communication between doctors and patients and their families of former members of the 2019 election KPPS in Pekanbaru City. The results of this study indicate that the patient's and patient's family assessed the communication that the doctor made while treating the patient was effective. This can be seen from the way doctors convey information to patients and their families, doctors are able to build a sense of secure and trust to the doctors which are the basic for effective communication.